PENGARUH SENAM AEROBIK TERHADAP PENURUNAN GEJALA PRAMENSTRUAL SYNDROME PADA REMAJA PUTRI DI SMPN 1 BANGKALAN - Novi Anggraeni (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Pramenstrual Syndrome is a troublesome physical, psychological and behavioral phenomenon that is not caused by organic disease, which regularly recurs during the cycle phase undergoing regression or disappearing during menstrual periods. The purpose of this study was to analyze the effect of decreased physical symptoms of pre menstrual syndrome before and after aerobic exercise on adolescent girls SMPN 1 Bangkalan. The research design used is Pre Experiment type One Group Pre-Test Post-Test Design. The dependent variable in this study is the physical symptoms of pramenstrual syndrome, whereas the independent variable is aerobic exercise. The population in this research is 45 people, with the sample number of 16 people in February 2017 in the working area of SMPN 1 Bangkalan, the sampling method using Probability Sampling by Simple Random Sampling, taking data using questionnaire sheet and using Wilcoxon Signed Rank Test The results showed that before aerobic exercise was given (87.5%) teenage girls experienced pramenstrual syndrome physical symptoms with moderate category and after given aerobic gymnastics most (81,25%) adolescent had physical symptoms of Pramenstral Syndrome with light category. Wilcoxon Signed Rank Test Analysis shows that α = 0,05 and ρ = 0,01 thus ρ <α so that H0 is rejected and Ha accepted that there is influence of aerobic gymnastics toward decreasing of physical symptoms of pre menstrual syndrome in juvenile girl SMPN 1 Bangkalan. The physical symptoms of Pramenstrual Syndrome, can be corrected by improving lifestyle changes such as aerobic exercise to reduce the symptoms that arise. Many other benefits of aerobic exercise for health such as increasing stamina and endurance